The dynamic behaviors of the Radhakrishnan-Kundu-Lakshmanan equation by Jacobi elliptic function expansion technique - Tarla, Sibel; Ali, Karmina K.; Yilmazer, Resat; Osman, M. S. (Springer, 2022)
In this study, we express the Radhakrishnan-Kundu-Lakshmanan equation with an arbitrary index of n is an element of Q. We investigated the solitary wave solutions of the Radhakrishnan-Kundu-Lakshmanan equation by mean of the Jacobi elliptic function expansion technique. As a result, we constructed several distinct solutions include dark, bright, singular, periodic, hyperbolic, trigonometric, and Jacobi elliptic function types solutions. To highlight the dynamic behavior of the generated solutions, specific values for the parameters are also assigned. The above techniques could also be employed to get a variety of exact solutions for other nonlinear models in physics, applied mathematics, and engineering.
Keywords: Radhakrishnan-Kundu-Lakshmanan equation; Jacobi elliptic function expansion technique; Analytical solutions; Optical solutions